Da poética á filosofia: o herói trágico em Prometeu e seu aspecto histórico na fundamentação da virtude no diálogo Protágoras de Platão - Almeida Júnior, José Donizett de (2017)
This work aims to present the myth of Prometheus as a fundamental circumstance for the beginning of the main discussion of all the dialogue in the Protagoras work. This work consists of a bibliographical research, in which we will use the conception of Paideia related to the myth of Prometheus with emphasis in the work Protagoras of Plato. We divide the work into three chapters that have a gradual construction, characterizing between them the notion of areta - virtue; from its cosmogonic conception to its foundation in the Socrates dialogues, in which it is possible to perceive the dialectics and the sophistry that are mixed, composing the whole scene of the thought of the time. Our first intention is not a technical approach in relation to the essential themes of ancient philosophy, but rather, an introduction in which, in the first moment, we will lead the reader to the appearance of the attic period until Hellenism, passing through tragediographers that exalted the image of the hero - like Prometheus, expressed by the manifestation of the Greek theater that represented the instrument of Paideia in Ancient Greece. Next, we direct the study to the understanding of the myth of Prometheus quoted by Protagoras in the homonymous dialogue. After the presentation and analysis of the work Prometheus Bound, one of the most important pieces written by Aeschylus, we have in the final part of this work the conduction of the dialogue of Protagoras and Socrates described by Plato. In this final part, we seek to clarify the relationship between Prometheus and areté, as a tempting sophistry of using the myth [digression of discourse] in favor of arguments about the nature of virtue, which will be the subject of discussion in the whole work, where both dialogues would change positions due to the rough form of the arguments presented in most of the text.